Elephants and human ecology in northeastern Ghana and northern Togo - Moses Sam; Richard Barnes (Pachyderm)
The amount and quality of habitat for elephants depends on the needs of human populations, and as the pressure on land continues to grow and soil fertility declines through over use the future of elephant populations in this region becomes increasingly difficult. Crop destruction by elephants is usually just prior to the harvest. If elephants are to survive in such a crowded landscape preparation of an effective land use plan requires a detailed study of agriculture, human ecology, and assessment of the populations of both elephant and human the land can support.